UVC disinfects SARS-CoV-2 by induction of viral genome damage without apparent effects on viral morphology and proteins - Chieh-Wen Lo (Nature Portfolio, 2021)
Abstract Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been a pandemic threat worldwide and causes severe health and economic burdens. Contaminated environments, such as personal items and room surfaces, are considered to have virus transmission potential. Ultraviolet C (UVC) light has demonstrated germicidal ability and removes environmental contamination. UVC has inactivated SARS-CoV-2; however, the underlying mechanisms are not clear. It was confirmed here that UVC 253.7 nm, with a dose of 500 μW/cm2, completely inactivated SARS-CoV-2 in a time-dependent manner and reduced virus infectivity by 10–4.9-fold within 30 s. Immunoblotting analysis for viral spike and nucleocapsid proteins showed that UVC treatment did not damage viral proteins. The viral particle morphology remained intact even when the virus completely lost infectivity after UVC irradiation, as observed by transmission electronic microscopy. In contrast, UVC irradiation-induced genome damage was identified using the newly developed long reverse-transcription quantitative-polymerase chain reaction (RT-qPCR) assay, but not conventional RT-qPCR. The six developed long RT-PCR assays that covered the full-length viral genome clearly indicated a negative correlation between virus infectivity and UVC irradiation-induced genome damage (R2 ranging from 0.75 to 0.96). Altogether, these results provide evidence that UVC inactivates SARS-CoV-2 through the induction of viral genome damage.